2013
DOI: 10.1186/1471-2350-14-98
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants associated with fasting glucose and insulin concentrations in an ethnically diverse population: results from the Population Architecture using Genomics and Epidemiology (PAGE) study

Abstract: BackgroundMultiple genome-wide association studies (GWAS) within European populations have implicated common genetic variants associated with insulin and glucose concentrations. In contrast, few studies have been conducted within minority groups, which carry the highest burden of impaired glucose homeostasis and type 2 diabetes in the U.S.MethodsAs part of the 'Population Architecture using Genomics and Epidemiology (PAGE) Consortium, we investigated the association of up to 10 GWAS-identified single nucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 24 publications
2
18
0
1
Order By: Relevance
“…Stressing the fact that FPG levels are not influenced by the same factors in children and adults is also important29. Our findings confirm that SNPs previously identified in specific ethnic groups are relevant candidates for association analyses in other populations1112303132.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Stressing the fact that FPG levels are not influenced by the same factors in children and adults is also important29. Our findings confirm that SNPs previously identified in specific ethnic groups are relevant candidates for association analyses in other populations1112303132.…”
Section: Discussionsupporting
confidence: 82%
“…This supports the view that the genetic dissection of both extremes of the disease and intermediary quantitative traits is necessary for the understanding of glucose homeostasis9. FPG-associated loci identified in European populations were in part replicated in various ethnic groups101112. Only one study to date have assessed the contribution of GWAS identified European adult FPG-associated loci in a youth population13.…”
supporting
confidence: 53%
“…Transethnic studies show that genetic determinants of type 2 diabetes risk or glycaemic trait levels in whites also operate in African-Americans, albeit at varying allele frequencies; thus, absolute genetic differences between racial/ethnic groups in glycaemic trait levels or disease risk are generally small [1318]. For instance, African-American type 2 diabetes admixture mapping is consistent with an independent effect of African ancestry proportion on type 2 diabetes risk but not on diabetes-related quantitative trait levels (such as fasting glucose [FG], insulin or HbA 1c ) in non-diabetic individuals [12].…”
Section: Introductionmentioning
confidence: 99%
“…After failing to find association between a number of such genetic risk variants and T2D in African Americans (with the exception of certain variants in the TCF7L2 gene), Lewis et al (2008) concluded that the T2D susceptibility genes in African Americans may, in part, be different from those identified in the European-derived populations. In recent years, there have been continued efforts to examine the transferability of the established GWAS T2D and/ or glycemic trait loci in the US multiethnic populations with considerable affirmations Haiman et al 2012;Fesinmeyer et al 2013;. In recent years, there have been continued efforts to examine the transferability of the established GWAS T2D and/ or glycemic trait loci in the US multiethnic populations with considerable affirmations Haiman et al 2012;Fesinmeyer et al 2013;.…”
Section: Replication Of T2d Susceptibility Loci Identified By Gwass Imentioning
confidence: 99%